(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The requirements for knowledge, skills and qualifications of students in higher education institutions are of great importance in the formation of higher education and the training of specialists. These requirements are determined both at the level of state and educational authorities, and at the level of a specific educational institution.